2018
DOI: 10.1017/s1355617718000383
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis of Executive Functions in Preschool and School-Age Children With Neurofibromatosis Type 1

Abstract: Objectives:Neurofibromatosis type 1 (NF1) is a genetic disorder in which the most frequent complication in children is learning disabilities. Over the past decade, growing arguments support the idea that executive dysfunction is a core deficit in children with NF1. However, some data remain inconsistent. The aim of this study was to determine the magnitude of impairment for each executive function (EF) and clarify the impact of methodological choices and participant’s characteristics on EFs.Methods:In this met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 69 publications
2
31
1
1
Order By: Relevance
“…-Language disabilities in about 50% of the cases, especially in phonological processes (2). -Attention deficit according to the diagnostic criteria for Attention Deficit and Hyperactivity Disorder (ADHD) in 30 to 40% of the cases (3, 4), and in general, executive function deficits (5). -Social cognition deficit, sometimes with the Autism Spectrum Disorder (ASD) criteria (6).…”
Section: Introductionmentioning
confidence: 99%
“…-Language disabilities in about 50% of the cases, especially in phonological processes (2). -Attention deficit according to the diagnostic criteria for Attention Deficit and Hyperactivity Disorder (ADHD) in 30 to 40% of the cases (3, 4), and in general, executive function deficits (5). -Social cognition deficit, sometimes with the Autism Spectrum Disorder (ASD) criteria (6).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, executive dysfunction has been noted on performance measures as well. Beaussart et al [50] conducted a meta-analysis of executive functioning in children with NF1. They included 19 studies in their analysis, with a total of 805 children with NF1 and 667 control subjects.…”
Section: Executive Functionsmentioning
confidence: 99%
“…Several studies have documented verbal and visual working memory weaknesses [10,14,49]. Beaussart et al [50] found a moderate to large effect size for working memory problems. The effect size for verbal working memory was larger than nonverbal working memory.…”
Section: Executive Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by the core symptoms of inattention, hyperactivity, and impulsivity [19] affecting 2.6–4.5 percent of children worldwide [20]. Children with ADHD display deficits in several cognitive domains ranging from simple alertness performance to intellectual capacities [2124]. Besides this, ADHD is accompanied by subjective sleep complaints [2528].…”
Section: Introductionmentioning
confidence: 99%